From my perspective: Perceived participation in mainstream schools in students with autism spectrum conditions - Falkmer, Marita; Granlund, M.; Nilholm, C.; Falkmer, Torbjorn (Informa Healthcare, 2012)
Objectives: To examine perceived participation in students with ASC and their classmates in mainstream schools and to investigate correlations between activities the students wanted to do and actually participated in. Methods: Twenty-two students with ASC and their 382 classmates responded to a 46-item questionnaire regarding perceived participation in mainstream schools. Results: On 57% of the items, students with ASC perceived lower participation than their classmates. These results emphasize the importance of knowledge about students’ perceived participation. However, positive correlations between what the students wanted to do and actually did indicate that students with ASC may be participating to the extent that they wanted. Conclusion: Students with ASC perceived lower overall participation in mainstream school than their classmates. The correlations between “I want to” and “I do” statements in students with ASC indicated that aspects of autonomy are important to incorporate when studying, and interpreting, self-rated participation in mainstream schools.